Detection of virulence genes, phylogenetic group and antibiotic resistance of uropathogenic Escherichia coli in Mongolia - Munkhdelger, Yandag; Gunregjav, Nyamaa; Dorjpurev, Altantsetseg; Juniichiro, Nishi; Sarantuya, Jav (The Journal of Infection in Developing Countries, 2017)
Introduction: The severity of urinary tract infection (UTI) produced by uropathogenic Escherichia coli (UPEC) is due to the expression of a wide spectrum of virulence genes. E. coli strains were divided into four phylogenetic groups (A, B1, B2 and D) based on their virulence genes. The present study aimed to assess the relationship between virulence genes, phylogenetic groups, and antibiotic resistance of UPEC. Methodology: A total of 148 E. coli were tested for antimicrobial resistance against 10 drugs using the disk diffusion method. The isolates were screened by polymerase chain reaction (PCR) for detection of virulence genes and categorized into the four major phylogenetic groups. Results: Phylogenetic group B2 was predominant (33.8%), followed by D (28.4%), A (19.6), and B1 (18.2%). A higher prevalence of fimH (89.9%), fyuA (70.3%), traT (66.2%), iutA (62.2%), kpsMTII (58.8%), and aer (56.1%) genes were found in UPEC, indicating a putative role of adhesins, iron acquisition systems, and protectins that are main cause of UTIs. The most common antibiotic resistance was to cephalotin (85.1%), ampicillin (78.4%) and the least to nitrofurantoin (5.4%) and imipenem (2%). In total, 93.9% of isolates were multidrug resistant (MDR). Conclusions: This study showed that group B2 and D were the predominant phylogenetic groups and virulence-associated genes were mostly distributed in these groups. The virulence genes encoding components of adhesins, iron acquisition systems, and protectins were highly prevalent among antibiotic-resistant UPEC. Although the majority of strains are MDR, nitrofurantoin is the drug of choice for treatment of UTI patients in Ulaanbaatar.